Breast reconstruction and risk of arm lymphedema development: A meta-analysis. Issue 6 (June 2018) - Siotos, Charalampos; Sebai, Mohamad E.; Wan, Eric L.; Bello, Ricardo J.; Habibi, Mehran; Cooney, Damon S.; Manahan, Michele A.; Cooney, Carisa M.; Seal, Stella M.; Rosson, Gedge D.
Summary: Background: Lymphedema remains a significant complication following breast cancer surgery when there is axillary lymph node intervention. Previous systematic reviews have identified risk factors for breast cancer-related lymphedema, including increased BMI, number of lymph nodes dissected and radiotherapy. However, they have not examined the effect of breast reconstruction on lymphedema occurrence. In this systematic review and meta-analysis, we sought to evaluate the association between breast reconstruction (BR) and lymphedema. Methods: We searched PubMed (1966–2016), Embase (1966–2016), Scopus (2004–2016) and Google Scholar (2004–2016) for studies involving breast reconstruction and upper-extremity lymphedema or breast cancer-related lymphedema. Our primary outcome was lymphedema occurrence. We performed a meta-analysis using random effects due to heterogeneity of the studies. Results: Our search strategy identified 934 articles. After screening, 19 studies were included in our meta-analysis evaluating outcomes based on number of patients (7501) or number of breasts surgically treated (2063). Breast reconstruction was significantly associated with lower odds of lymphedema (p < 0.001) compared to mastectomy only or breast-conserving surgery. Lymphedema rates were not statistically significantly different between patients undergoing implant-based or autologous BR. Conclusions: Breast reconstruction is associated with lower rates of lymphedema compared to mastectomy only or breast conserving surgery patients. Although the study does not prove causation, we hypothesize that this association is likely due to multiple factors, including a self-selecting population and mechanisms through which BR may contribute to primary or secondary prevention of lymphedema. Further prospective studies are needed to clarify this beneficial relationship between breast reconstruction and reduced lymphedema risk.